The Changing Perception of the African Woman towards Patriarchy and Masculinity (International Journal of Scientific Research and Management (IJSRM), 2020)
Patriarchy is a social structure in which men are the primary holders of power, and are preponderate in roles of local authority, political leadership, economic power and control of property. Several African literary productions focus on the suffering of women in such patriarchal setup with men being very domineering and women oppressed; the man is always at the helm with the woman being the silent observer. In most cases, property and family name are passed down within the male line of inheritance. Basically, men are in charge. This article however exposes the changing awareness of today’s African woman from one who is governed to being more in control of her surroundings. Using two African plays: Ola Rotimi’s Our Husband Has Gone Mad Again and Anne Tanyi Tang’s Eneta vs Elimo, we argue that women have evolved from being disenfranchised dependents and voiceless recipients to assertive and productive contributors in their families and society. Deconstruction and Nego-feminism are applied here to reveal how women negotiate their way through patriarchy as a means of achieving their goals of empowerment and determination to effect socio-political change.